DEVELOPMENT OF COMPUTER-AIDED LEARNING MEDIA ON VIBRATION AND WAVE MATERIAL, IMPROVE STUDENTS' CONCEPT UNDERSTANDING GRADE 8 - Faudina Permatasari; Vindhy Dian Indah Pratika (JoEICT (Jurnal of Education And ICT), 2023)
This research aims to develop computer-assisted learning media that is feasible and valid so that it can visualize abstract concepts in vibration and wave material for junior high school / MTs class VIII students. The development method used in this research and development is the Four-D Model by taking three steps, namely defining, designing, and developing. The feasibility of the developed media can be known from the validation test and the readability test. The results of the development in the form of computer-aided learning media on vibration and wave material for students in grade VIII SMP / MTs. The results of the feasibility test by media experts obtained an average score of 93.25% which means very feasible. The test results by material experts obtained 20 correct concepts, all of which are very feasible, and the results of the readability test obtained an average score of 93.75%, all respondents can accept this media well, which means it is very feasible. Based on the results of the assessment, in general, the learning media developed has met the criteria very feasible so that it can be said that learning media can help improve concept understanding for students.